Characterization of Corneal Donor Tissue Lesions by Anterior Segment Optical Coherence Tomography Compared With Eye Bank Technician Slit-Lamp Examination. Issue 10 (October 2018) - Hsu, S. Tammy; Perry, Isaac; Botsay, Sara; Ko, Narae; Stinnett, Sandra S.; Kuo, Anthony N.; Shieh, Christine
Abstract : Purpose: To compare anterior segment spectral-domain optical coherence tomography (OCT) with eye bank technician slit-lamp examination (SLE) in characterizing lesions in donor corneas. Methods: Twenty-nine donor corneas identified by eye bank technicians to have opacities or lesions potentially representing pathologic findings affecting the stroma were evaluated through the use of technician SLE, SLE photography, and OCT. Technicians were tasked with describing the lesion, estimating the lesion depth, and photographing their SLE findings. A masked grader evaluated the OCT images and measured the lesion depth using customized software. The lesions identified on OCT were then compared with those identified on SLE. Results: A total of 37 lesions were detected on SLE; 25 of the 37 lesions identified on SLE were matched to a lesion on OCT. SLE and OCT depth measurements were statistically significantly different ( P = 0.0042, mean difference 4.8% ± 6.5%), and OCT graded lesions as slightly deeper. Of the 12 out of the 37 lesions that were noted on SLE (but not identified on OCT), these included 2 central and paracentral anterior stromal lesions (OCT showed loose epithelium), 5 peripheral anterior stromal lesions, and 5 corneas with LASIK. Conclusions: Our study highlights both advantages and limitations of OCT compared with technician SLE in the evaluation of donor corneal tissue. Although OCT may miss some peripheral lesions and LASIK scars that are identifiable on SLE, OCT's depth resolution is helpful in differentiating whether shallow anterior opacities actually extend deeper into the stroma or are confined superficially to the epithelium.